Strategi Implementasi Pencantuman Informasi Kandungan Gula, Garam, dan Lemak untuk Pencegahan Risiko Penyakit Tidak Menular - Stefanus Indrayana; Nurheni Sri Palupi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
In Indonesia, the growth of food processing industry and ready to eat food/dishes follow the growth of fast-food outlets, fast-food chains, and restaurants. The changes of food consumption pattern in Indonesian consumers is shown by the increase in consumption of processed and fast foods rich in energy, high in sugar, salt, and fat, but low in fiber. Combined with the lack of physical activities or exercise, there may be an increase in non-communicable diseases (NCD) risks. The role of all stakeholders is needed to protect consumers from NCD risks, particularly hypertension, stroke and coronary heart disease, which are partly due to excessive intake of sugar, salt, and fat. In response to this problem, the Ministry of Health has issued a regulation on the Inclusion of Information on Sugar, Salt, and Fats (SSF) Contents (# 30/2013), as well as Health Messages for Processed and Ready to Eat Food. The government has also launched the 2014 Nutrition Balance Guideline. To support its implementation, the business sector can play a significant role in the form of food product reformulation/development, consumer education about the importance of food labeling reading and understanding, as well as providing a clear nutritional information in a more appealing way as it may help consumer decision making when buying processed food products. Educational institutions in all levels can play an active role through its education program, such as course content enrichment. The synergic role between the government, businesses, and educational institutions in educating consumer effectively is essential to minimize NCD risks.